2009
DOI: 10.1021/pr800960n
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Transglutaminase 2-Mediated Deamidation of Gluten Peptides: Implications for the T-cell Response in Celiac Disease

Abstract: Celiac disease develops in genetically predisposed individuals as the result of an inappropriate intestinal immune response to dietary gluten proteins. T cells present in the intestine of celiac patients recognize gluten peptides in the context of HLA-DQ2 or -DQ8 molecules. Notably, T-cell recognition is increased after these peptides have been deamidated by the enzyme transglutaminase 2. Several T-cell epitopes of gluten exist, and most of these epitopes derive from the alcohol-soluble gliadin fraction. For s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 92 publications
(181 reference statements)
3
30
0
1
Order By: Relevance
“…Variant peptides that displayed a serine (S) at position 5 instead of an phenylalaninine (F) were found to have lost T-cell stimulatory capacity. Moreover, the presence of a positively charged arginine (R) residue at position +1 diminished T-cell proliferation (Additional file 3), most likely because it influenced the deamidation of Q9 as previously observed by Dørum et al [28]. Similarly, a tryptophan (W) at position +2 inhibited the T-cell response (Additional file 3).…”
Section: Discussionsupporting
confidence: 57%
“…Variant peptides that displayed a serine (S) at position 5 instead of an phenylalaninine (F) were found to have lost T-cell stimulatory capacity. Moreover, the presence of a positively charged arginine (R) residue at position +1 diminished T-cell proliferation (Additional file 3), most likely because it influenced the deamidation of Q9 as previously observed by Dørum et al [28]. Similarly, a tryptophan (W) at position +2 inhibited the T-cell response (Additional file 3).…”
Section: Discussionsupporting
confidence: 57%
“…TGase-mediated glutamine deamidation is a well known PTM found in dietary gluten protein, which in turn results in an increased T-cell response (44). The high glutamine substrate affinity for TGase cross-linking found in Tau protein is of particular interest here (45), because glutamine deamidation may trigger misfolding of Tau (46), ␣-synuclein, and Huntington protein.…”
Section: Discussionmentioning
confidence: 99%
“…Only glutamine residues residing in the sequence QXP, where Q is glutamine, X is any amino acid and P is proline, are targeted by the enzyme [35,36], providing yet an explanation for the high proline content in gluten T-cell epitopes. Interestingly, it was found that those peptides that are most efficiently deamidated are also the ones that are most frequently recognized by T cells in celiac disease patients [37], pointing at a central role for TG2 in shaping the anti-gluten T-cell repertoire. This was signified by the finding that within a complex mixture of gluten peptides, TG2 selectively targeted peptides harboring known T-cell epitopes [38].…”
Section: Substrate Affinity To Transglutaminase-2 (Tg2)mentioning
confidence: 99%